Variations of Tween Surfactant and Propylene Glycol Cosurfactant in Topical Microemulsion Formulation on The Penetration of Ibuprofen - Sri Fitrianingsih; Gunawan Pamudji Widodo; Dian Marlina (Universitas Pakuan, 2022)
ABSTRACTIbuprofen is a derivative of propionic acid, a class of non-steroidal anti-inflammatory drugs (NSAIDs). Ibuprofen has side effects on the gastrointestinal tract. So that topical use can be a solution to reduce the side effects of oral use because of the release of topical drugs through the stratum corneum which makes it selective in certain places. The preparation chosen was a topical microemulsion because it is more thermodynamically stable and has no effect on the gastrointestinal tract. This study aims to determine the effect of the ratio of surfactant concentrations of various ratios of tween 20:tween 80 and cosurfactant propylene glycol to the penetration rate of ibuprofen across the membrane and to determine the physical characteristics of topical microemulsions. Selection of tween surfactant and propylene glycol cosurfactant because it has high physical stability. This research is an experimental study, namely by making four formulations with various ratios of surfactant and cosurfactant with a difference of 2.5% in each formulation of topical ibuprofen microemulsion with a concentration of 5% ibuprofen using variations of surfactant tween 20 and tween 80, cosurfactant propylene glycol with black cumin oil phase. Evaluation of the preparation by organoleptic test, pH test of the preparation, examination of the type of emulsion, particle size measurement, microemulsion release test in vitro using the Franz diffusion method. The results show that the concentration ratio of surfactant tween 20:tween 80 and cosurfactant propylene glycol can affect particle size, pH and penetration velocity (flux) in Franz diffusion. The results of the study showed that in F1 using surfactant tween 20:tween 80 with a concentration of 71.6% (6:4) had the smallest particle size of 11.5 nm and the largest flux value was 128.45 g.cm-2.H- 1. In conclusion, variations in surfactant and cosurfactant concentrations can affect the pH of the preparation, particle size, penetration speed (flux). The results obtained that the cumulative percent and penetration speed of all formulas had significant differences (p0.05).